Breakthrough or Continuation? Slovak Political Thought after 1867). - Goszczyńska, Joanna (Poznańskie Studia Slawistyczne, 2019)
The article focuses on two texts (Jozef Podhradský, The secret history of Pan-Slavism and Michal Miloslav Hodža Vieroslavín), that are located on the periphery of Slovak political thought, but they are a very significant testimony to the intersection of emancipation ideas in the period of dualistic monarchy. These important texts bring a proposal of various solutions to the arrangement of Slovak-Hungarian relations in the new situation after 1867. Unfortunately, one of them was not published at all (written by Hodža in 1867–1870), while the second one, published in Novi Sad in 1868, remained almost unnoticed. They show how close the idea of messianism was to Slovak thinkers at that time. (This particularly applies to M.M. Hodža). Under her influence, they present their visions of Europe and the monarchy. They also show the Slovaks as a chosen nation that will play a decisive role in the revive common Europe.